Robustness in monetary policymaking: a case for the Friedman rule - Juha Kilponen; Kai Leitemo (Bank of Finland, 2006)
Inflation targeting involves using all available information in stabilizing inflation around some target rate (Svensson, 2003). Inflation is typically at the very end of the transmission mechanism and hence its determination is subject to much model uncertainty which the central bank will want to guard against using robust policies. Such robustness comes however with the cost of increased social loss under the most likely description of the economy. We show that with a sufficiently high degree of model uncertainty, adherence to the Friedman rule of increasing the money stock by k percent will be superior as the price paid for robustness is smaller.
URN:NBN:fi:bof-201501291023
Keywords: E42; E52; E58; E61; 330; policy robustness; money growth targeting; inflation targeting; Friedman rule